2023
DOI: 10.1002/mcda.1818
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the sustainable development: A review of multi‐criteria decision analysis for urban and architectural sustainability

Abstract: Sustainable development of cities constitutes nowadays a worldwide goal. Therefore, the related urban and architectural choices must fulfil sustainable objectives. In this context, sustainability assessment presents itself as a key and fundamental element to guide decision‐making processes, orienting choices towards actions that make the built environment more sustainable. Among the several existing assessment tools and methods, multi‐criteria decision analysis (MCDA) are part of the most widely used approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…Also, MCDA methods, as the review revealed, are mostly used in combination with other techniques, as they cannot provide objective or definitive answers on their own, and other evaluation methods are also needed to provide reliable impact assessments [11]. AHP emerges as the most applied method, given the simplicity of application, through the support of the available software (Expert Choice) [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, MCDA methods, as the review revealed, are mostly used in combination with other techniques, as they cannot provide objective or definitive answers on their own, and other evaluation methods are also needed to provide reliable impact assessments [11]. AHP emerges as the most applied method, given the simplicity of application, through the support of the available software (Expert Choice) [38].…”
Section: Discussionmentioning
confidence: 99%
“…The choice to use one method over another is not arbitrary but depends on the specific problem and users' needs [19]. In particular, MCDAs have progressively assumed a central role in supporting sustainable decisions [20,37,38], gaining wide acceptance with respect to their combination with other instruments, such as the aforementioned LCA, ecological footprints, and environmental indicators [29]. Specifically, the Analytic Hierarchy Process (AHP) [39] emerged in various studies related to waste management systems, mainly depending on the LCA method's environmental scores [11,40].…”
Section: Multi-criteria Approaches To the Sustainability Assessment O...mentioning
confidence: 99%
“…In this work, we have chosen to apply multicriteria evaluation techniques. The procedure applied by Barredo and Gómez [49] is followed, which is based on the contributions of various authors who have provided the scientific foundations for these procedures and techniques [50][51][52][53]. The evaluation process starts with the selection of the factors to be included in the evaluation and the scoring of their values.…”
Section: Assessment Of the Territorial Adequacy Of The Urban Process ...mentioning
confidence: 99%
“…Scientifically evaluating and planning design schemes with different foci from multiple perspectives is the key to green design [14,15]. Currently, many scholars are conducting research in the areas of energy, environment, supply chain management, manufacturing, land use management, and other areas of sustainable development in conjunction with the multi-criteria decision-making (MCDM) approach [16][17][18]. Zhang et al [19] proposed a hybrid approach combining the Decision-Making Trial and Evaluation Laboratory (DEMATEL), Analytic Network Process (ANP), Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), and Grey Relational Analysis (GRA) to select the desired optimal sustainable green materials.…”
Section: Introductionmentioning
confidence: 99%